A study of potency determination of 3C antimuonium crudum in the treatment of corn - Kumar, Rekha; Prajapati, Aarti; Prajapati, Pooja (International Journal of Advances in Medicine, 2024)
Background: Planter skin is anatomically different from the normal skin of the body due to prominence of keratin filaments such as k6, k7, k9, k16 and k17. As per Hahnemann statement in chronic disease, Antimuonium crudum is basically the native ore (persulphuric of antimony) found in blocks of parallel block needle with a metallic lustre and are composed of twenty-eight parts of sulphur combined with 100 parts of metallic antimony. Methods: An observational comparative prospective open label study was conducted from September 2019 to September 2020. 32 patients were included in the study. Follow up of the cases were done after every 15 days where the size of the corn was measured using a vernier caliper. Height, width and diameter of the corn was also measured pre and post-treatment to analyse the results. Results: A total of 32 patients were studied. The size of the corn was considerably reduced after taking the medication. There was a significant reduction in the intensity of the pain due to corn after medication as well. Conclusions: There is a significant reduction of disease intensity score, after the homoeopathic treatment. Which shows the efficacy and potency of 3C Antimuonium crudum in the treatment of corn.